Management of patient with head injuries during the first 24 hours in Princess Marina Hospital (Botswana) - Gwaila, Tebogo Synat (My University, 2014)
The purpose fo the study was to investigate and describe the documented management of head injured patients during the first 24 hours as implemented at the Princess Marina Hospital, Gaborone (Botswana). Particular attention was paid to the documented interventions carried out by nurses and medical doctors during the first 24 hours. A survey research design using a chekclist to obtain data was utilized.The method of data collection was by record review. The population for this research comprised all head injured patients admitted to the Princess Marina Hospital over a one year period from 1.1.1997 to 31.12.1997. A preliminary record review indicated that a total of 240 patients have been treated from January 1997 to December 1991 The sample (n = 126) consisted of one hundred and twenty-six records of head injured patients, who were received in the accident and emergency unit and admitted in different wards for m anagem ent during the first 24 hours. The setting of this research was the Princess Marina Hospital in Gaborone, Botswana. A pilot study was undertaken at the sam e hospital. Data was analysed by use of a computer. Descriptive statistics were used. The study revealed that documentation of time of injury, arrival time and time of transfer to the wards was inadequate. Motor vehicle accidents are the commonest causes of injury and assault is the second commonest. Though poor documentation is noted at som e stages, adequate care appears to have been given to patients in the opinion of the researcher. The prescription and interventions for head injured patients were found to be appropriate. There was poor documentation on cervical spine c o n tro l. Blood g ases were not assessed in 98% of patients.